Customer Value-Based Marketing Strategy: A Case Study of PT Sharp Electronics Indonesia in Improving Loyalty and Brand Image - Ibrahim, Asep Warsa (Universitas Muhammadiyah Tangerang, 2025)
This research focuses on customer value as a key component in modern marketing strategy, with a case analysis of Sharp Electronics Indonesia Corp. With the development of technology, companies need to adapt strategies to provide optimal value to customers through relevant products and services. This research uses descriptive qualitative methods to identify customer value-based marketing practices that focus on product quality, innovation, and responsive service. Primary data was obtained from observations of Sharp's marketing activities, while secondary data from related literature. The findings show that customer value plays an important role in driving consumer loyalty and satisfaction. Sharp, through approaches such as utilization of digital channels, loyalty programs, and product customization for the local market, strengthens its position in the market and improves brand image. This research recommends practical strategies for businesses looking to strengthen customer loyalty and engagement through a customer value-oriented marketing approach